Case Report: The immune architecture of immunotherapy-induced cutaneous sarcoidosis resembles peritumoral inflammation - Wang, Catherine J.; Strong, Jennifer; Gatti-Mays, Margaret E.; Lassoued, Wiem; Sater, Sam; Strauss, Julius; Redman, Jason M.; Schlom, Jeffrey; Gulley, James L.; Brownell, Isaac (Frontiers in Immunology, 2025)
Avelumab, is an anti-PD-L1 immune checkpoint inhibitor (ICI). Like other ICI, avelumab can cause immune-related adverse events. Although rare, sarcoidosis-like granulomatous reactions have been described in patients on anti-CTLA-4 and anti-PD-1 immunotherapy. Here we report a case of treatment emergent cutaneous sarcoidosis in a patient who received avelumab for metastatic colon cancer. A 56-year-old African American woman with metastatic colon cancer that had progressed after multiple lines of treatment, including other immunotherapy agents, was enrolled on a clinical trial with avelumab. While on treatment, the patient developed two skin lesions, and histopathological examination of both biopsies demonstrated chronic granulomatous inflammation in the dermis with multinucleated giant cells containing asteroid bodies, consistent with cutaneous sarcoidosis. Multiplex immunofluorescence revealed parallels between the immune architecture of the patient’s cutaneous sarcoidal lesion and an excised tumor metastasis. Recognizing cutaneous sarcoidosis as a rare adverse effect of ICI immunotherapy is important because sarcoidal lesions can be mistaken for metastatic disease on clinical exam and medical imaging. We noticed similar immune composition of the sarcoidal granuloma and tumor microenvironment. However, further studies are needed to fully elucidate the mechanism of ICI associated sarcoidosis.